The Effect Of Octane Breast Massage on Milk Production, Neonatus Weight Gain, and Breast Congestion: Literature Review - Ida Maryati; Farras Gapa Fauziyyah; Grisela Parisa Rahim; Syipa Izzati Hermawan; Zahra Siti Hanifah (Universitas Malahayati Lampung, 2023)
ABSTRACT Breast care is an effort to stimulate the secretion of the hormones oxytocin and prolactin to produce breast milk as early as possible and play an important role in dealing with breastfeeding problems. Breast milk is one of the important components for mothers to pay attention to because it contains colostrum, and this colostrum contains many antibodies for the baby's immune system, so exclusive breastfeeding is very important to reduce the risk of disease and death in infants. Octane massage can increase milk production because it can stimulate the strength of the pectoralis muscle. This study aims to describe the effect of an Octane Breast Massage on a mother's milk production. This research method is a literature study in search of article data sources carried out through Pubmed, EBSCO-host, ScienceDirect, Springer, Garuda, and Google Scholar (2017-2022) to retrieve relevant articles published in English and Indonesian with the type of quasi-experimental and randomized controlled trial. Based on a literature study of 7 research articles with the duration of the intervention starting from the fastest 3 days and the longest being 14 days, it was found that the octane massage intervention was effective for the smooth production of breast milk. Keywords: Breast Milk Production, Octane, Postpartum